Financial Management Behavior Analysis in Student of The Department Management UPN “Veteran” Jawa Timur - Mentari Clara Dewanti; Daisy Marthina Rosyanti; Fani Khoirotunnisa (Nusantara Science and Technology Proceedings, 2022)
Financial knowledge is learned by Generation Z students through lectures, seminars, and training activities carried out by campuses and off-campus institutions that are still considered less able to be applied optimally, this is shown through the lack of responsibility for students to apply the knowledge they get in their daily financial behavior. This study tries to examine financial management in Generation Z, namely students majoring in management at the Faculty of Economics and Business UPN "Veteran" Jawa Timur. The approach to this research is qualitative which is used to find out and provide an overview of the reality of financial management behavior by Generation Z students. Data collection techniques through conservation, interviews, and documentation studies on students. Based on the results of this study states that students are less able to manage their finances because they are faced with unwise decisions in terms of financial management.